A SOURCE-CRITICAL ANALYSIS OF THE PERSON AND LEGACY OF BURHANUDDIN AL-NASAFI - Bakhromov Sunnatilla Khamidjon ugli (Sciental Journals Publishing, 2025)
This article investigates the historical problems surrounding the personality and legacy of the 13th-century Mawarannahr mutakallim (theologian) Burhanuddin al-Nasafi (approx. 600/1203–687/1288). The analysis focuses on the discrepancy between the scarcity of biographical data on al-Nasafi (especially regarding his teachers) and his high reputation as the “Sheikh of Baghdad's philosophy”. The article substantiates his affiliation with the Maturidi school through his views on the issue of “the faith of the muqallid” (iman al-muqallid). Furthermore, it reveals the reasons for the centuries-old bibliographical confusion surrounding his major works, such as “Kashf al-Haqa'iq” (tafsir) and “al-Fusul al-Burhaniya” (jadal), including their erroneous attribution to other authors (like Fakhruddin al-Razi and Muwaffaquddin al-Kawashi), and presents methodological evidence proving his true authorship.
Keywords: Burhanuddin al-Nasafi, 13th-century Mawarannahr, Hanafi jurisprudence, Kalam and Philosophy, Source criticism, Historiographical problems, Attribution confusion, Fakhruddin al-Razi, Muwaffaquddin al-Kawashi, “Sheikh of Baghdad's philosophy”.